Novel inhibitors to ADP ribose phosphatase of SARS-CoV-2 identified by structure-based high throughput virtual screening and molecular dynamics simulations. (January 2022) - Patel, Dhrumi C.; Hausman, Katherine R.; Arba, Muhammad; Tran, Annie; Lakernick, Phillip M.; Wu, Chun
Abstract: The outbreak of a new coronavirus (SARS-CoV-2) was first identified in Wuhan, People's Republic of China, in 2019, which has led to a severe, life-threatening form of pneumonia (COVID-19). Research scientists all around the world have been trying to find small molecule drugs to treat COVID-19. In the present study, a conserved macrodomain, ADP Ribose phosphatase (ADRP), of a critical non-structural protein (Nsp3) in all coronaviruses was probed using large-scale Molecular Dynamics (MD) simulations to identify novel inhibitors. In our virtual screening workflow, the recently-solved X-ray complex structure, 6W6Y, with a substrate-mimics was used to screen 17 million ZINC15 compounds using drug property filters and Glide docking scores. The top twenty output compounds each underwent 200 ns MD simulations (i.e. 20 × 200 ns) to validate their individual stability as potential inhibitors. Eight out of the twenty compounds showed stable binding modes in the MD simulations, as well as favorable drug properties from our predctions. Therefore, our computational data suggest that the resulting top eight out of twenty compounds could potentially be novel inhibitors to ADRP of SARS-CoV-2. Highlights: The NSP3 containing ADRP/macrodomain of SARS-CoV-2 was targeted by 17 million zinc15 compounds. Top 20 compounds have good docking scores to bind with macrodomain of nsp3 8 compounds are shown to be potential inhibitors of ADP-ribose phosphatase of nsp3 of SARS-CoV-2 based on their improved MM-GBSA binding free energy score.